A highly active (102) surface-induced rapid degradation of a CuS nanotheranostic platform for in situ T1-weighted magnetic resonance imaging-guided synergistic therapy. Issue 27 (2nd July 2019) - Dong, Lile; Li, Kai; Wen, Ding; Lu, Yu; Du, Kaimin; Zhang, Manli; Gao, Xuan; Feng, Jing; Zhang, Hongjie
Abstract : CuS nanocrystals with pH and near-infrared light-triggered degradation properties are promising nanotheranostic platform for in situ T 1 -weighted MRI guided synergistic therapy of cancer. Abstract : Polyvinylpyrrolidone-modified CuS nanocrystals (CuS NCs) with high photothermal conversion efficiency (46%) and pH and near-infrared (NIR) light-triggered degradation properties are a promising nanotheranostic platform for in situ magnetic resonance imaging (MRI)-guided synergistic photothermal and photodynamic therapy. On the one hand, the (102) surface of CuS NCs has a small bandgap based on density functional theory, which leads to high photothermal conversion efficiency. On the other hand, the S vacancy formation energy of the (102) surface is favourable. On entry into tumor cells through endocytosis, the S 2− ions on the (102) surface of CuS NCs can be easily oxidized under the tumor microenvironment and 808 nm laser irradiation; then, a large amount of Cu + ions can be released from CuS NCs and accelerate the degradation of nanocrystals. Cu + ions can generate reactive oxygen species (ROS) under the tumor microenvironment and 808 nm laser irradiation. Meanwhile, the oxidation product Cu 2+ ions can be generated from the oxidized Cu + ions and applied for in situ T 1 -weighted magnetic resonance imaging. Moreover, the biodegradable CuS NCs possess a high tumor uptake and can be rapidly excreted with a low long-term retention/toxicity. Therefore, degradable and multifunctional CuS NCs are a safe and efficient candidate for the diagnosis and treatment of cancer.